Non-ST-Elevation Acute Myocardial Infarction and Sustained Slow Ventricular Tachycardia due to Coronary Slow Flow Phenomenon: a Case Report - Baiq Gerisa Rahmi Faharani; Anggoro Budi Hartopo; Nahar Taufiq (Faculty of Medicine, Public Health and Nursing Universitas Gadjah Mada, 2019)
Coronary slow flow is a phenomenon that is found in coronary angiography.It is a rare case and identified by the corrected TIMI frame count. The presence of a slow flow in the coronary arteries is associated with life-threatening arrhythmias, sudden death, andacute coronary syndrome. We aim to report a coronary slow flow phenomenon present with non-ST-elevation acute myocardial infarction and sustained slow ventricular tachycardia in 66-year-old male patient. Brief heparinisation and continued by oral acetosal, ticagrelor, bisoprolol and atorvastatin therapy successfully diminish the symptom.